BACTERIAL SYMBIONT BIOACTIVE COMPOUND OF SOFT CORAL Sinularia flexibilis AND S. polydactyla - . Rozirwan; Dietriech G. Bengen; . Chaidir; Neviaty P. Zamani; Hefni Effendi (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2015)
Symbiont bacteria on soft coral can produce bioactive compounds that plays an important role in chemical ecology and as a marine natural product. The purpose of this study was to find and characterize the antibacterial activities of active compounds extracted from bacterial symbionts of soft coral S. flexibilis and S. polydactyla. The methods used in this study were culture and isolation of bacterial symbionts, extraction of compounds, antibacterial bioassay, and identification of bioactive compounds using the LC-MS analyses. Four isolates of bacterial symbionts were obtained from two samples of soft corals, 2 isolates of Pseudomonas diminuta (A1) and Edwardsiellla hoshinae (A2) from soft coral S. flexibilis, and 2 isolates of E. hoshinae (B1) and P. acidovorans (B4) from S. polydactila. Antibacterial activity were found only from the extracts of bacterial symbionts P. diminuta (A1) and from  S. flexiblis about 10.16 ± 0.3mm (for B. subtilis), 8.66 ± 0.8 mm (E. coli) and 9.86 ± 1.7mm (S. dysentri). No antibacterial activity found from the extracts of S. polydactyla. The results of LC MS analysis showed that the group of diterpenes sinularin produced by soft corals S. flexibilis and bacterial symbionts isolates of P. diminuta (A1).Keywords:  Bacterial Symbiont, Bioactive Compound, Antibacterial Activity, Soft Coral, Sinularia flexibilis, Sinularia polydactyla